Development of Mechanical Ventilation Systems ‘Smart Vehicle Ventilation’ on Vehicles Using IoT - Wan Mohd Akmal Jayati; rahim, mohd bekri; Debie Devisser Gerijih; Yunus, Faizal Amin Nur; Ali, Khairul Fahmi; Abdul Rahman, Khairul Anuar; Razali, Nizamuddin (Research and Innovation in Technical and Vocational Education and Training, 2021)
TThe present study aims to develop the mechanical ventilation system for vehicle based on IoT technology. The system is developed by using the ADDIE model which consist of five main elements. They are Analysis, Design, Development, Implementation and Evaluation. The main goal focuses on the development of this product which produces mechanical ventilation systems used in vehicles and controlled using IoT to get rid of heat which is trapped in vehicles when parked under sun radiation. This is due to the trapped temperature can exceed 48 ℃. In fact, the body temperature exceeding 40 ℃ can also provide the risk of suffering from heat stroke. Therefore, the main purpose of the researcher is to develop this product to prevent vehicle users from experiencing heat stroke. The results show that by using the ventilation systems, the process of heat removal in the vehicle can be increase up to maximum of 16.7% and minimum of 7.0%. Installation of this ventilation system is alternately a cost-effective, environmentally friendly and energy-efficient method for removing heat in vehicles. Based on expert reviews and suggestions, enhancement of this study is to use the correct CFM based on cabin size and product design appropriate to space in the vehicle.